Preschool Curriculum System Innovation in the Philippines and Indonesia: Inovasi Sistem Kurikulum Prasekolah di Filipina dan Indonesia - Nur Cahyati Ngaisah; Firman Priyo Suhasto; Kulsum Nur Hayati (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2022)
The curriculum system in education becomes one of the identities of various countries. The Philippines and Indonesia have different curricula from multiple factors in realizing the nation's ideals, to educate generations who are experts in their fields. The purpose of this research is to find out the curriculum innovations applied in the educational process both domestically and abroad, one of them is the Philippines which possesses excellence in various educational programs. This research uses a qualitative approach with a literature study method that uses secondary data from multiple national and international journal articles. As for the data analysis technique, it uses qualitative analysis techniques in a deductive way from discussing the preschool education system converging into the curriculum used in the Philippines and Indonesia. The findings from this study are that the education system in Indonesia has almost the same quality as foreign countries. The Philippines designed the K-12 curriculum implemented in preschool by developing various aspects of child development to prepare the child to enter primary school. While in Indonesian curriculum prepares children with disabilities in cognitive development so that they ignore other developments because several elementary school institutions require children to be able to read, write and count. Abstrak Sistem kurikulum dalam pendidikan menjadikan salah satu identitas dari berbagai negara. Filipina dan Indonesia memiliki kurikulum yang berbeda dari berbagai faktor dalam mengujudkan cita-cita bangsa, untuk mencerdaskan generasi-generasi yang ahli dibidang kemampuannya. Tujuan dari penelitian ini yaitu untuk mengetahui inovasi kurikulum yang digunakan dalam proses pendidikan baik di dalam negeri maupun luar negeri, salah satunya yaitu negara Filipina yang memiliki keunggulan diberbagai program pendidikan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka yang menggunakan data sekunder dari berbagai artikel jurnal nasional dan internasional. Sedangkan untuk teknik analisis data menggunakan teknik analisa kualitatif dengan cara deduktif dari pembahasan sistem pendidikan prasekolah merucut kedalam kurikulum yang digunakan di negara Filipina dan Indonesia. Temuan dari penelitian ini bahwa sistem pendidikan di Indonesia memiliki kualitas yang hampir sama dengan kurikulum mancanegara. Filipina merancang kurikulum K-12 yang diterapkan prasekolah dengan mengembangkan berbagai aspek perkembangan anak untuk mempersiapkan anak ke jenjang Sekolah Dasar. Dan Indonesia untuk mempersiapkan anak terfokus pada perkembangan kognitif sehingga mengabaikan perkembangan yang lain karena beberapa lembaga Sekolah Dasar yang menuntut anak sudah bisa membaca, menulis dan berhitung.